An asymmetric burden: Experiences of men and women as caregivers of people with psycho-social disabilities in rural North India. (February 2019) - Mathias, Kaaren; Kermode, Michelle; San Sebastian, Miguel; Davar, Bhargavi; Goicolea, Isabel
Caring for a family member with a psycho-social disability can be both rewarding and burdensome. This study analyses the experiences of caregivers of people with psychosocial disabilities (PPSDs) in rural communities in North India using relational gender theory. In-depth interviews with 18 female and male caregivers of PPSDs probed the social, emotional and health impacts of their caregiving role. Nine themes were identified that were grouped under three meta-themes: intra-personal, inter-personal and institutional impacts. Under the intra-personal meta-theme, all caregivers experienced high tension, with women describing almost overwhelming stress. Women minimised their role as caregivers, and felt negative and hopeless about their futures, while men had a more positive view of the future and themselves. Embodied experiences of psychological and social distress were consistently described by women, but not by men. Within the interpersonal meta-theme, men experienced opportunity for social connection and social support that was seldom available to women. Interpersonal violence with other household members was described by both men and women. Within the institutional meta-theme, both men and women described strength in unity, and gestures leading to the reordering of gender relations. These findings underline the significant and diffuse impacts of a gender order that values males and disadvantages females as caregivers of PPSDs, with the asymmetry of a greater burden for women. The findings point to the urgent need for global mental health policies that support and empower caregivers and that strengthen gender equality.